Pemanfaatan Youtbe Sebagai Media Pembelajaran dalam Jaringan Masa Pandemi Covid-19 di Sekolah Dasar (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This study aims to describe: Utilization of Youtube as a Learning Media in the Covid-19 Pandemic Period in Class II SDN 12 Tungkal Ilir, Tungkal Ilir District, Banyuasin Regency in 2020/2021.This research is described in a qualitative descriptive manner with a phenomenological type of research that describes the use of YouTube in learning for class II students at SDN 12 Tungkal Ilir, Tungkal Ilir District, Banyuasin Regency in 2020/2021. The data from this study were obtained through interviews with students using the sampling method and also participation. as well as students' understanding of the material through YouTube, observation in the form of passive participation observation and documentation as supporting data from the results of interviews.The results of the study show that teachers have used YouTube as a learning medium in supporting online learning activities by utilizing various available features such as video descriptions, Thumbnail adjustments, playlists, schedules, Share Links, and end screens. Then in the use of YouTube as a learning medium, it was declared that it was effectively used as a learning medium in the network during the Covid-19 pandemic. In addition, the use of YouTube is also able to increase students' understanding of learning materials.